EPIDEMIOLOGICAL PROFILE OF CASES OF SEXUAL VIOLENCE IN ANÁPOLIS Â€“ GÓIAS, BETWEEN 2017 AND 2020 (CIPEEX, 2022)
SEXUAL VIOLENCE CAN BE CHARACTERIZED AS ANY ACTION IN WHICH A PERSON, IN A RELATIONSHIP OF POWER, THROUGH PHYSICAL FORCE, COERCION, SEDUCTION OR PSYCHOLOGICAL SUBPOENA, FORCES ANOTHER PERSON TO PRACTICE OR SUBMIT TO SEXUAL INTERCOURSE OR SITUATIONS THAT MAY HARM THE PHYSICAL AND/OR MORAL INTEGRITY OF THE VICTIM. THEREFORE, THE PRESENT STUDY AIMED TO DETERMINE THE EPIDEMIOLOGICAL PROFILE OF VICTIMS WHO SUFFERED SEXUAL VIOLENCE, DESCRIBED IN THE NOTIFICATION AND DISEASES INFORMATION SYSTEM (SINAN) IN ANÁPOLIS - GO BETWEEN THE YEARS 2017 AND 2020. THIS IS A STUDY EPIDEMIOLOGICAL, DESCRIPTIVE OF A QUANTITATIVE APPROACH THAT TOOK AS A SOURCE OF INFORMATION THE CASES OF SEXUAL VIOLENCE AGAINST WOMEN, CHILDREN AND ADOLESCENTS, OF BOTH SEXES, LINKED TO THE DEPARTMENT OF EPIDEMIOLOGICAL SURVEILLANCE OF THE MUNICIPAL HEALTH DEPARTMENT OF ANÁPOLIS/GO. A TOTAL OF 850 CASES WERE REPORTED, WITH A PREDOMINANCE OF FEMALE VICTIMS (82.1%), AGED BETWEEN 2 AND 10 YEARS (42.2%), OF MIXED RACE (61.2%), WITH INCOMPLETE ELEMENTARY SCHOOL EDUCATION/ COMPLETE (33.5%), SINGLE (37.1%), AND THE MOST COMMON CONDUCT AFTER SEXUAL VIOLENCE WAS BLOOD COLLECTION (20%); THE MAIN AGGRESSORS WERE THE PARENTS (20.9%), THE PLACE OF AGGRESSION THAT HAD THE MOST VICTIMS WAS AT HOME (75.2%), THE MAIN TYPE OF SEXUAL VIOLENCE WAS RAPE (68.7%) AND THE VICTIMS WERE REFERRED , MAINLY FOR THE GUARDIANSHIP COUNCIL (48.2%). THE VICTIMS WERE WOMEN, CHILDREN, ADOLESCENTS, BROWN, SINGLE, WITH INCOMPLETE/COMPLETED ELEMENTARY SCHOOLING AND WERE ASSAULTED, MAINLY, BY THEIR PARENTS.
Keywords: sexual violence; descriptive epidemiology; compulsory abuse notification